Computational Study on the Interactions of Mustard Gas with Cucurbituril Macrocycles - Venkataramanan, Natarajan Sathiyamoorthy; Suvitha, Ambigapathy; Mizuseki, Hiroshi; Kawazoe, Yoshiyuki (John Wiley & Sons Inc., 2015)
The study on the absorption of toxic gases such as mustard gas by organic host is essential to the development of inexpensive detection and decontamination equipments. Using quantum chemical methods, we propose cucurbituril as an effective host to capture mustard gas. It was found that stable complexes are formed with the inclusion of the toxic gas molecules inside the cucurbituril cavity, compared with the lateral and exterior interactions. Oxygen mustard has a comparable binding energy with sulfur mustard and hence can be used during experimental investigation. Additionally, during the inclusion complex formation, the presence of heteroatoms helps the guest molecules to undergo a larger structural reorganization to get accommodated inside the cucurbituril macromolecule. Atoms-in-molecules analysis shows the existence of strong intermolecular CH center dot center dot center dot O bonding between the guest molecules and cucurbituril macromolecule. The presence of an intramolecular CH center dot center dot center dot Cl type of bonding accounts for the higher stabilization of sulfur mustard inside the cucurbituril macromolecule. (C) 2015 Wiley Periodicals, Inc.